Mandibula Tumor Dextra Et Causa Ameloblastoma : A Case Report - Diska Astarini; Christian O. Manginstar; Marcelus Merung (Lembaga Pengembangan Kinerja Dosen, 2026)
Ameloblastoma is a benign but locally aggressive odontogenic tumor that commonly arises in the mandible, especially in the posterior region. Despite its histologically benign nature, it can cause significant facial deformity, functional impairment, and high recurrence if inadequately treated. Diagnosis requires a combination of imaging studies and histopathological confirmation. We reported a case of a 22-year-old male who presented with a progressively enlarging painless swelling in the right lower jaw over five years. CT scan revealed a large, well-demarcated, expansile radiolucent lesion measuring 14 × 16 cm in the right mandibular region with signs of cortical destruction. Panoramic radiograph showed multilocular radiolucency with ill-defined margins and root displacement. Physical examination revealed a firm, fixed mass without lymphadenopathy. The patient underwent right hemimandibulectomy with mandibular reconstruction using a plate and screws. Histopathological analysis confirmed a multicystic ameloblastoma. Postoperative recovery was uneventful, and the patient demonstrated satisfactory functional and aesthetic outcomes. This case illustrates the typical clinical and radiological features of multicystic ameloblastoma and highlights the importance of early diagnosis and radical surgical excision. Multicystic ameloblastoma, while benign, shows locally invasive behavior that necessitates segmental resection with clear margins. The absence of lymph node involvement and distant metastasis in this case is consistent with the benign nature of the tumor. Long-term follow-up is essential due to the high risk of recurrence.Early identification and comprehensive surgical management of ameloblastoma are critical to preventing extensive bone destruction and functional compromise. Hemimandibulectomy with reconstruction remains the definitive treatment in large, locally aggressive mandibular ameloblastomas. This case adds to the literature on ameloblastoma management and supports the role of early intervention and long-term monitoring.